Do mothers of children with autism are at higher risk of depression? a systematic review of literature - AlHorany, Ahmed Kamel; Ahmad Younis, Najati; Bataineh, Marwan Zaid; Hassan, Siti Aishah (Marsland Press, 2013)
We aimed to systematically review studies that examine factors affecting depression among parents of children with disabilities, especially, the autistic children. Besides, we emphasized the effects of gender on depression among the parents. There were at least 27 articles reviewed. The related journal articles on factor affecting depression were downloaded with cut off limit from 1997 to 2013. The articles were then analyzed and organized according to the definitions of depression and various factor affecting depression. We found there was no conclusive evidence regarding the factors affecting the depression among parents of children with autism. There was conclusive evidence from the reviewed literature regarding gender effect, yet the number of article supporting it was small. Mothers of children with autism were more affected in the depression as compared to fathers. Finally, with conclusion we then suggest for future interventional study.